Optimalisasi Strategi Pengembangan Sumber Daya Manusia Dalam Meningkatkan Efektivitas Pelayanan Publik di Era Digital 2045 - Leni Rohida; Siti Khumayah; Hagies Ferdiansyah Akbar (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
To respond to the challenges and needs of contemporary society, the public sector must rapidly adapt to digital transformation. The objective of this research is to examine relevant and adaptive human resource development strategies for the digital ecosystem and to evaluate how they impact the quality of public services in the era of technological disruption. This research uses a descriptive qualitative approach with a literature review and policy analysis. It analyzes best practices from government institutions, both national and international, in developing human resources oriented towards the digital era. Key findings indicate that optimizing human resources requires not only improving technological capabilities or digital expertise; it also requires reconstructing leadership paradigms, flexible organizational cultures, and implementing meritocratic systems and data-driven performance management. It is evident that technologies such as big data analytics, artificial intelligence (AI), and the Internet of Things (IoT) can help improve public services, but the success of these technologies depends heavily on the capabilities and readiness of the employees who manage these systems. An integrated digital talent ecosystem must be built, encompassing continuous training (learning for life), collaboration between government, academia, and business (the triple helix model), and a regulatory framework responsive to technological developments. Furthermore, it is emphasized that developing digital integrity and ethics is crucial as a pillar of good governance in the digital era. Optimizing human resource development strategies systematically and sustainably will enable Indonesia to improve the efficiency of public services and strengthen the competitiveness of its bureaucracy globally. By 2045, adaptable, innovative, and highly integrated human resources will be the primary drivers of a digital government transformation that is inclusive, responsive, and future-oriented.